2020
DOI: 10.1371/journal.pcbi.1007874
|View full text |Cite
|
Sign up to set email alerts
|

Simulating flow induced migration in vascular remodelling

Abstract: Shear stress induces directed endothelial cell (EC) migration in blood vessels leading to vessel diameter increase and induction of vascular maturation. Other factors, such as EC elongation and interaction between ECs and non-vascular areas are also important. Computational models have previously been used to study collective cell migration. These models can be used to predict EC migration and its effect on vascular remodelling during embryogenesis. We combined live time-lapse imaging of the remodelling vascul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 44 publications
0
16
1
Order By: Relevance
“…The concept of “set point theory” in vascular remodelling proposes that ECs seek an optimal amount of shear stress, and deviations away from this optimal level promote a change from quiescence to the remodelling phenotype ( Baeyens and Schwartz, 2016 ). Further, there is evidence that EC migration speed follows a “band pass-like” behaviour as a function of shear stress in which EC migration slows down and stops all together for shear stress values that are too high or low flow ( Tabibian et al, 2020 ). This complicated relationship between migration speeds and shear stress could result in the “locking in” of ECs within vessels with exceptionally high or low shear stress (the latter of which may be relevant inside of large diameter AVMs) and result in a gradient of migration speeds across the vascular plexus (from venous to arterial) during remodelling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of “set point theory” in vascular remodelling proposes that ECs seek an optimal amount of shear stress, and deviations away from this optimal level promote a change from quiescence to the remodelling phenotype ( Baeyens and Schwartz, 2016 ). Further, there is evidence that EC migration speed follows a “band pass-like” behaviour as a function of shear stress in which EC migration slows down and stops all together for shear stress values that are too high or low flow ( Tabibian et al, 2020 ). This complicated relationship between migration speeds and shear stress could result in the “locking in” of ECs within vessels with exceptionally high or low shear stress (the latter of which may be relevant inside of large diameter AVMs) and result in a gradient of migration speeds across the vascular plexus (from venous to arterial) during remodelling.…”
Section: Discussionmentioning
confidence: 99%
“…This behaviour could be implemented in our model in future studies by describing the migration force parameter as a function of stress. We chose an elliptical representation of ECs as Tabibian et al demonstrated that EC elongation was a critical aspect of angiogenic remodelling ( Tabibian et al, 2020 ). However, in this current study we kept the extend of elongation constant; in future studies it might be interesting to vary the extent of EC elongation as a function of shear stress and other singalling regulators.…”
Section: Discussionmentioning
confidence: 99%
“…It relates both to the speed of the blood flow and vessel geometry. In the migration paradigm of vessel enlargement, endothelial cells migrate against flow when shear stress levels are decreased compared to physiological normal levels (which are 15 dyn/cm 2 in humans or 30 dyn/cm 2 in mouse) and stop migrating in the presence of physiological levels ( Franco et al, 2015 ; Tabibian et al, 2020 ). Therefore, vessels with the lowest flow rates regress increasing the pool of available endothelial cells.…”
Section: Mechanisms Of Vessel Enlargementmentioning
confidence: 99%
“…Our group has recently used the migration-induced mechanism of vessel enlargement to develop computational models of remodeling and vessel enlargement ( Tabibian et al, 2020 ). In vitro , we found that there is indeed a bell-shaped pattern of migration with respect to shear stress.…”
Section: Mechanisms Of Vessel Enlargementmentioning
confidence: 99%
See 1 more Smart Citation